An interorganizational IT infrastructure for self-organization in logistics: situation awareness and real-time chain composition. Issue 2 (3rd May 2016) - Hofman, Wout; Punter, Matthijs; Bastiaansen, Harrie; Cornelisse, Erik; Dalmolen, Simon; Palaskas, Zisis; Karakostas, Bill; Gato, Jose; Garcia, Javier; Herrero, Germán; Gonzalez-Rodriguez, Marta
Abstract : To meet the challenges for more sustainable, effective and efficient transport services in global logistics, a new IT-paradigm is needed to harvest the opportunities that capabilities for situation awareness and real-time chain composition provide. The iCargo project provides such an advanced, highly distributed, IT infrastructure with, as fundamental features: a highly distributed "system-of-systems" implementation with a minimum of centralized functionality, referred to as the "Hybrid Services Network" (HSN); virtualization of the IT infrastructure (HSN) to shield the user from the complexities of the highly distributed implementation through the use of "access points"; seamless interoperability by means of semantic technology deployed through semantic gateways. This paper elaborates these aspects of an interorganizational IT infrastructure for logistics. Additionally, the migration towards this innovative and advanced infrastructure is addressed.